ANALISIS POLITIK PADA KASUS KORUPSI DI KEMENTERIAN PERTANIAN TAHUN 2023 - , Mahira Wijaya Bekti Artadi; Dian Suluh Kusuma Dewi (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
There is a corruption case involving the former Minister of Agriculture from 2020 to 2023, Syahrul Yasin Limpo. It is known that Syahrul Yasin Limpo is an elite cadre of the Nasdem party, raising suspicions of fund flows to the party participating in the upcoming presidential contest in the 2024 elections. The corruption in the Ministry of Agriculture has caused a financial loss to the state amounting to 13.9 billion Indonesian Rupiah. This journal article aims to analyze the corruption case that occurred in the Ministry of Agriculture in 2023. By employing a qualitative descriptive research method with a literature study approach using the NVIVO application, the study aims to gather data that is still evolving. The research indicates that Syahrul Yasin Limpo utilized his power to establish an informal structure and a special team to accomplish his mission. There are suspicions of fund flows to the party for campaign financing, which, as of now, cannot be clearly proven due to the absence of specific regulations governing such matters.